Pendekatan Antropologis dalam Studi Islam - Harahap, Asriana; Kahpi, Mhd. Latip (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2021)
Anthropology is the science of humans, especially about the origin, various colors of physical form, customs, and beliefs in the past. Epithemologically, anthropology studies various things about humans empirically in their relationship as biological beings and as social beings (in the sense of living in society). The method that is more appropriate with the anthropological approach is the holistic method. This means that seeing a social phenomenon must be examined in the context of the totality of the studied community culture. Meanwhile, the most appropriate data collection techniques are involved observation (observation) and in-depth interviews, that is, directly mingling in the community being studied.